O032 Simultaneous liver and thoracic transplantation: outcomes in a specialist centre in the United Kingdom. (22nd July 2022) - Malik, AK; Dark, J; Wilson, CH; Sen, G; Talbot, D; Masson, S; Hassan, A; White, SA; Manas, DM
Abstract: Introduction: Operative and logistical complexity of combined heart-liver (HLTx) and combined lung-liver (LLTx) transplantation limit the wider adoption of such a specialist procedure. We report a consecutive series of patients who underwent simultaneous liver and thoracic transplants Methods: We performed a retrospective review of patients undergoing combined liver and thoracic transplantation from 2001–2021. Patients were discussed at a joint liver-thoracic multi-disciplinary team meeting Perioperative care was managed jointly by liver and thoracic anaesthetic teams. Immunosuppression was guided by cardiothoracic protocols. Results: Seven patients (5M:2F, age range 21–54) underwent HLTx/LLTx. Four underwent HLTx transplantation whereas 3 underwent LLTx, all combined with a simultaneous liver transplant. Indications for HLTx were failing Fontan circulations with associated liver cirrhosis (n=3) and failing Fontan circulation with solitary 6.6 cm hepatocellular carcinoma treated with 5 rounds of trans-arterial chemoembolization pre-transplantation (n=1). Indications for LLTx were cystic fibrosis with associated cirrhosis (n=2) and alpha-1 antitrypsin deficiency (n=1). The following complications were also managed; for HLTx biliary stricture needing hepaticojejunostomy (n=1), sternal debridement (n=1), re-sternotomy for haemodynamic compromise (n=1), and for LLTx endoscopic management of a biliary stricture (n=1). There was one mortality in the series in a HLTx who was highly sensitised and developed acute rejection with multiorgan failure and died on day 12. The remaining six patients are alive and well following transplantation, with follow-up ranging from 8 months to 15 years. Conclusion: Combined liver and thoracic transplants are a high-risk intervention, but can produce acceptable outcomes in selected patients despite the complexity and logistical issues. Take-home message: Combined liver and thoracic transplantation is a complex procedure, suitable for selected patients and performed in a specialist centre to achieve acceptable outcomes.